ANTI-INFLAMMATORY EFFECT OF PORTERWEED (Stachytarpheta Jamaicensis (L.) Vahl) LEAF EXTRACT TO TNF-α EXPRESSION - Anastya Eka Kharisma; Hendra Susanto; Muhammad Rifqi Hariri (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2012)
Porterweed (Stachytarpheta jamaicensis (L.) Vahl) contain many fl avonoids compound. It is a potential candidate to supress the inflammatory process through down regulation of TNF-α level as a potent pro-infl ammatory cytokine in chronic infl ammation cases. The aim of this research was to improve the effect of Porterweed leaf extract to the TNF-α level and considered the optimum dosage in wistar rats with chronic infl ammation model. Twenty fi ve rats was divided into negative control group, positive control group, and treatment groups with dosage 50, 100 and 150 mg/kg BW. Data obtained through microscopical histologic observation on aortic organafter immunohistochemistry staining and was analyzed descriptively. The result revealed that Porterweed leaf extract is able to inhibit the increasing of TNF-α level. This phytochemical substance is predicted capable of preventing the oxidation reaction progession ofcyclooxygenase-2 (COX-2) to produce prostaglandins. The decreasing of prostaglandin level causes a negative feedback to TNF-α production and iniciating the declining level of TNF-α. Thus, the Porterweed leaf extract indicates supress chronic infl ammatory process through down regulation of TNF-α and prostaglandin activity in optimum dose 150 mg/kg bw.